2016
DOI: 10.1017/s1473550415000555
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation effects on antibody performance in the frame of biochip-based instruments development for space exploration

Abstract: International audienceSeveral instruments based on immunoassay techniques have been proposed for life-detection experiments in the framework of planetary exploration but few experiments have been conducted so far to test the resistance of antibodies against cosmic ray particles. We present several irradiation experiments carried out on both grafted and free antibodies for different types of incident particles (protons, neutrons, electrons and 12C) at different energies (between 9 MeV and 50 MeV) and different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…To improve the understanding of Ab surfaces resistance to space hazards in real-space constraints with cumulative effects, full-length Ab-NHS surfaces were chosen to be exposed outside the International Space Station on the EXPOSE-R2 platform (Vigier et al 2013;Cottin et al 2014). In recent results (Baqué et al 2015), our group demonstrated that Ab surfaces should have a higher density than the fluence of incident particles in order to minimize the radiation effects on Ab performances. Since DGL(G3/ G4) surfaces help to increase the number of immobilized Abs, the Ab-DGL(G3/G4) surfaces could be proposed in future exobiology experiments.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To improve the understanding of Ab surfaces resistance to space hazards in real-space constraints with cumulative effects, full-length Ab-NHS surfaces were chosen to be exposed outside the International Space Station on the EXPOSE-R2 platform (Vigier et al 2013;Cottin et al 2014). In recent results (Baqué et al 2015), our group demonstrated that Ab surfaces should have a higher density than the fluence of incident particles in order to minimize the radiation effects on Ab performances. Since DGL(G3/ G4) surfaces help to increase the number of immobilized Abs, the Ab-DGL(G3/G4) surfaces could be proposed in future exobiology experiments.…”
Section: Discussionmentioning
confidence: 99%
“…For protons, five different energies (14.4, 20.9, 25.9, 29.4 and 50.5 MeV) and two fluences (3 × 10 11 and 3 × 10 12 protons cm −2 ) were used. All the parameters are described in detail in Baqué et al (2015).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations